Contaminant or goldmine? In silico assessment of Symbiodiniaceae community using coral hologenomes - Ishida, Hisatake; Riginos, Cynthia; Chan, Cheong Xin (Frontiers in Protistology, 2024)
Endosymbiotic dinoflagellates of the family Symbiodiniaceae are symbionts essential to corals and other marine organisms. A coral holobiont consists of the coral host, Symbiodiniaceae, and other microbes that together sustain the overall productivity and coral health. Coral hologenome data, generated from all interacting components of a coral holobiont, are key for elucidating the molecular mechanisms that underpin the resilience of the holobiont to changing environments. Although coral hologenome data are often dominated by host coral genomic sequences, they provide an avenue for recovering genomic sequences from Symbiodiniaceae in hospite. Here, we review recent advances in the approaches for assessing community diversity of in hospite Symbiodiniaceae from coral hologenome data. Using a case study based on existing hologenome datasets of the Acropora kenti coral, we highlight how hologenome datasets in large numbers can provide a useful analysis platform for assessing Symbiodiniaceae diversity and their function in coral holobionts.